2001
DOI: 10.1254/jjp.87.34
|View full text |Cite
|
Sign up to set email alerts
|

Antiischemic Properties of Fasudil in Experimental Models of Vasospastic Angina

Abstract: ABSTRACT-We studied the antiischemic properties of fasudil, a Rho-kinase inhibitor, in conscious rabbits with coronary vasospasm induced by vasopressin and endothelin. Pretreatment with fasudil (0.3 and 3 mg/kg) attenuated the maximum elevation of the T-wave elicited by endothelin. Pretreatment with fasudil inhibited the T-wave elevation elicited by vasopressin. Fasudil and hydroxy fasudil, an active metabolite of fasudil, relaxed the endothelin-, U-46619-, 5-hydroxytryptamine-or histamine-induced contraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 21 publications
(16 reference statements)
1
17
0
Order By: Relevance
“…In agreement with our findings, inhibition of the Rho/ROK pathway blunted ET-1-induced vasoconstriction in mammary, mesenteric, penile, cerebral, and coronary arteries (8,(35)(36)(37)(38). Preventing coronary artery vasospasm in response to ET-1, ROK inhibition protected against myocardial ischemia in rabbits (13,39).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with our findings, inhibition of the Rho/ROK pathway blunted ET-1-induced vasoconstriction in mammary, mesenteric, penile, cerebral, and coronary arteries (8,(35)(36)(37)(38). Preventing coronary artery vasospasm in response to ET-1, ROK inhibition protected against myocardial ischemia in rabbits (13,39).…”
Section: Discussionsupporting
confidence: 91%
“…A recently developed ROK inhibitor, the pyridine derivative Y-27632, has been shown to potently inhibit the contraction of preparations from experimental animals and human arterial vessels induced by different agonists in vitro and also to correct arterial pressure to normotensive levels in different experimental models of hypertension in vivo (8 -11). Because of the evidence that the Rho/ROK pathway mediates tonic vasoconstriction, ROK is thought to play a crucial role in human diseases, e.g., in hypertension and myocardial ischemia (12,13). The contribution of the ROK pathway to renal vasoconstriction is practically unknown.…”
mentioning
confidence: 99%
“…We demonstrated that pretreatment with fasudil before reperfusion prevents endothelial dysfunction and reduces the extent of myocardial infarction in dogs in vivo. 213 The beneficial effect of fasudil has also been demonstrated in a rabbit model of myocardial ischemia induced by intravenous administration of endothelin-1, 214 a canine model of pacing-induced myocardial ischemia, 215 and a rat model of vasopressin-induced chronic myocardial ischemia. January 22, 2016…”
Section: Rho-kinase In Cardiac Hypertrophy and Failurementioning
confidence: 98%
“…We have demonstrated that pretreatment with fasudil before reperfusion prevents endothelial dysfunction and reduces the extent of myocardial infarction in dogs in vivo. 132 The beneficial effect of fasudil has also been demonstrated in a rabbit model of myocardial ischemia induced by intravenous administration of endothelin-1, 133 a canine model of pacing-induced myocardial ischemia, 134 and a rat model of vasopressin-induced chronic myocardial ischemia.…”
Section: Aortic Aneurysmmentioning
confidence: 98%